Diversity and systematics of Haminoeidae gastropods (Heterobranchia: Cephalaspidea) in the tropical West Pacific Ocean: new data on the genera Aliculastrum, Atys, Diniatys and Liloa - Too, Chin Chin; Carlson, Clay; Hoff, Patty Jo; Malaquias, Manuel António E. (Zootaxa, 2014)
Four genera of Haminoeidae gastropods inhabiting the tropical West Pacific (Aliculastrum, Atys, Diniatys, and Liloa) were studied based on the combined analyses of live animals, external morphology, anatomy and shells aided by scanning electron microscopy and molecular sequencing. Eleven species are described including two new to Science, namely Atys pittmani sp. nov. and Atys ukulele sp. nov.. The putative synapomorphies of the genera Aliculastrum, Diniatys, and Liloa are discussed. High levels of morpho-anatomical variability were found among representatives of the genus Atys, which hampered the recognition of synapomorphies.